The effectiveness of transcutaneous electrical nerve stimulation in the management of patients with complex regional pain syndrome: A randomized, double-blinded, placebo-controlled prospective study - (:unkn) unknown (IOS PRESS, 2016)
OBJECTIVE: To investigate the effect of transcutaneous electrical nerve stimulation (TENS) on clinical recovery in the management of patients with complex regional pain syndrome Type I (CRPS Type I). MATERIAL AND METHOD: The study included 30 patients with stage 1 and 2 CRPS Type I in the upper extremities. The patients were randomly assigned into 2 groups, group 1 (n = 15) received conventional TENS therapy for 20 minutes, and group 2 (n = 15) received sham TENS therapy. The standard physical therapy program, which included contrast bath for 20 minutes; whirlpool bath for 15 minutes; assisted active and passive range of motion, and static stretching exercises up to the pain threshold, was also conducted in both groups. Therapy was scheduled for 15 sessions. A visual analogue scale (VAS) was used to assess spontaneous pain. The Leeds Assessment of Neuropathic Signs and Symptoms (LANSS) scale and the Douleur Neuropathique en 4 Questions (DN-4) were used to assess neuropathic pain. In addition, range of motion (ROM) was measured using a goniometer and volumetric measurements were taken to assess edema. Functional capacity was assessed using a hand dynamometer and the Duruoz Hand Index (DHI). All measurements were performed at baseline and after therapy. RESULTS: Significant improvements were achieved in spontaneous and neuropathic pain scores, edema, ROM, and functional capacity in both groups (p < 0.05). However, improvement was found to be significantly greater in group 1 regarding pain intensity, neuropathic pain assessed using LANNS, edema, and in the 2nd-3rd finger ROM measurements (p < 0.05). No significant difference was detected between groups regarding improvements in 4th-5th finger and wrist ROM measurements, grip strength, and DN4 and DHI scores (p > 0.05). CONCLUSION: The addition of TENS to the physical therapy program was seen to make a significant contribution to clinical recovery in CRPS Type 1.
Keywords: Complex regional pain syndrome; transcutaneous electrical nerve stimulation; pain; functional capacity; REFLEX SYMPATHETIC DYSTROPHY; NEUROPATHIC PAIN; PHYSICAL-THERAPY; HAND; VALIDATION; SCALE